Model Konseptual Untuk Penerapan Water Sensitive City Berdasarkan Kesehatan Ekologis Di Kota Sigli - Nurul Maulidia; Halis Agussaini; Fahmi Aulia (Universitas Syiah Kuala, 2023)
Sigli City experiences environmental problems such as floods, the lack of green open space as an infiltration area, to the existence of environmental-based diseases such as diarrhea which always occurs every year. Water Sensitive City (WSC) is a water-friendly city that supports the realization of sustainable development including protecting ecology and water resources. This study was conducted to determine the contribution of the seven WSC index targets in their implementation and identify the dominant factors that affect